Modified separation net, preparation method thereof and filter element containing modified separation net

By using modified spacers in nanofiltration filter elements, with the inner core being a polyolefin interwoven spacer and the outer layer being an ion gel structure, the problem of nanofiltration filter element clogging is solved, self-cleaning and anti-pollution capabilities are achieved, and the service life and water purification performance of the filter element are improved.

CN120618244APending Publication Date: 2025-09-12NINGBO FOTILE KITCHEN WARE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410281069.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-12
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing nanofiltration filter elements have the problem of fouling and clogging caused by pollutant enrichment during operation. The existing side flow technology has limited effect, complex process and harsh operating conditions. Nanofiltration membrane surface modification technology increases water flow resistance and affects water purification performance.

Method used

A modified separator is used, the inner core of which is a separator formed by interweaving polyolefins, and the outer layer is an ion gel. The ion gel composed of a cationic and anionic cross-linked network expands or contracts in water with different ionic strengths, has a self-cleaning function, and reduces the adhesion of pollutants.

Benefits of technology

The modified spacer has self-cleaning function and strong anti-pollution ability, which can protect the nanofiltration or reverse osmosis membrane and improve the filter element life and water purification performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120618244A_ABST
    Figure CN120618244A_ABST
Patent Text Reader

Abstract

The invention discloses a modified separation net, a preparation method thereof and a filter element containing the modified separation net. The modified separation net is composed of an inner core and an outer layer. The inner core is a separation net; the separation net is formed by interweaving polyolefin; tannic acid is adsorbed on the separation net; the outer layer is ionic gel; the thickness of the outer layer is 50 to 100 microns; the ionic gel comprises a cationic cross-linked network and an anionic cross-linked network; the cationic cross-linked network is formed by cross-linking reaction of polyethyleneimine and the tannic acid adsorbed on the separation net; the anionic cross-linked network is formed by a cross-linking reaction of 2-acrylamide-2-methylpropanesulfonic acid and diethylene glycol dimethacrylate; the cationic cross-linked network and the anionic cross-linked network are connected through glycidyl methacrylate. The modified separation net can reduce the adhesion capacity of pollutants, is high in anti-pollution capacity, and can also protect a nanofiltration or reverse osmosis membrane from being scratched.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of filtration and water purification, and in particular to a modified spacer and a preparation method thereof, and a filter element containing the same. Background Art

[0002] During the operation of the nanofiltration filter element, pollutants in tap water will continue to accumulate and deposit on the surface of the nanofiltration membrane and the screen, causing pollution and clogging of the nanofiltration membrane, thereby reducing the flow rate and life of the nanofiltration filter element. In order to increase the life of the nanofiltration filter element and reduce the pollution of the nanofiltration membrane surface, there are two main methods. One is the side flow technology, which mainly increases the flow rate on the membrane surface and extends the life of the filter element through the design of the filter element structure. The other is the nanofiltration membrane surface modification technology, which mainly introduces an anti-pollution coating on the surface of the nanofiltration membrane to reduce the adhesion of pollutants on the nanofiltration membrane surface, reduce the pollution of the nanofiltration membrane, and extend the service life of the nanofiltration membrane and filter element.

[0003] At present, there are major shortcomings in lateral flow technology. First, lateral flow technology has limited effect on slowing down the contamination of the nanofiltration membrane surface. Compared with conventional filter elements, the service life of side flow filter elements is usually increased by 10-20%, which is not much; second, compared with conventional filter elements, the membrane rolling process of lateral flow technology is complicated, and the sealing process at both ends needs to be added, which increases the process time and cost; finally, the use conditions of lateral flow technology are harsh. In a static state, when the fluid flow rate is zero, the side flow technology cannot slow down the contamination by increasing the fluid flow rate, so the effect of improving the life of the filter element is limited.

[0004] Nanofiltration membrane surface modification technology also has its shortcomings. Modifying the surface of the nanofiltration membrane and introducing an anti-pollution layer will increase the water flow resistance of the nanofiltration membrane, reduce the flux of the nanofiltration membrane, and directly affect the water purification performance of the nanofiltration membrane. Summary of the Invention

[0005] The present invention aims to overcome the shortcomings of existing technologies for mitigating contamination on the surface of nanofiltration membranes, such as poor mitigation effectiveness, complex processes, demanding operating conditions, and degradation of the membrane's performance. The invention provides a modified screen, a method for preparing the same, and a filter element containing the same. The modified screen reduces the adhesion of contaminants, exhibits strong anti-pollution capabilities, and protects nanofiltration or reverse osmosis membranes from scratches.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a modified separator, which consists of an inner core and an outer layer.

[0008] The inner core is a separator; the separator is formed by interweaving polyolefins; tannic acid is adsorbed on the separator;

[0009] The outer layer is an ion gel;

[0010] The thickness of the outer layer is 50-100 μm;

[0011] The ion gel comprises a cationic cross-linked network and an anionic cross-linked network;

[0012] The cationic cross-linked network is formed by a cross-linking reaction between polyethyleneimine and the tannic acid adsorbed on the separator;

[0013] The anionic cross-linked network is formed by the cross-linking reaction of 2-acrylamide-2-methylpropanesulfonic acid and diethanol dimethacrylate;

[0014] The cationic cross-linked network and the anionic cross-linked network are connected by glycidyl methacrylate.

[0015] In the present invention, the ion gel expands in water with low ionic strength and contracts in water with high ionic strength.

[0016] Preferably, the polyolefin is polypropylene.

[0017] More preferably, the molecular weight of the polypropylene is 30,000-150,000, and the degree of polymerization of the polypropylene is 714-3571.

[0018] Preferably, the diameter of the mesh of the separator is 0.1-0.5 mm, more preferably 0.3 mm-0.5 mm.

[0019] Preferably, the interweaving forming step is to extrude molten polyolefin through an extruder to obtain molten plastic filaments, and then interweave the plastic filaments to obtain a softened separator semi-finished product, and then cool and solidify it in a water bath.

[0020] Preferably, the thickness of the outer layer is 70-100 μm.

[0021] The present invention also provides a method for preparing a modified spacer, which specifically comprises the following steps:

[0022] S1. Soak the screen in an aqueous solution of tannic acid and polyethyleneimine;

[0023] Wherein, the separator is formed by interweaving polyolefins;

[0024] Wherein, the concentration of the tannic acid in the aqueous solution is 0.1-1 g / L;

[0025] Wherein, the concentration of the polyethyleneimine in the aqueous solution is 0.05-0.5 g / L;

[0026] S2. The spacer obtained in step S1 is soaked in an aqueous solution of glycidyl methacrylate;

[0027] Wherein, the concentration of glycidyl methacrylate in the aqueous solution is 10-20 g / L;

[0028] S3. The screen obtained in step S2 was soaked in a mixed solution of 2-acrylamide-2-methylpropanesulfonic acid, diethanol dimethacrylate and potassium persulfate;

[0029] Wherein, the concentration of the 2-acrylamide-2-methylpropanesulfonic acid in the mixed solution is 50-100 g / L;

[0030] Wherein, the concentration of diethyl dimethacrylate in the mixed solution is 10-20 g / L;

[0031] Wherein, the concentration of the potassium persulfate in the mixed solution is 3-5 g / L.

[0032] In the present invention, soaking means that the screen is completely immersed in the solution, for example, a screen with a mesh diameter of 0.1-0.5 mm per square meter is immersed in 2 L of solution.

[0033] In the present invention, 2-acrylamide-2-methylpropanesulfonic acid is negatively charged. In water with low ionic strength, the electrostatic repulsion of the negatively charged groups causes the ion gel to be stretched, and the ion gel is in an expanded state. On the contrary, in water with high ionic strength, the electrostatic repulsion of the negatively charged groups is shielded, and the ion gel collapses, and the ion gel is in a contracted state. When the filter element is in a stationary state, the ion gel on the surface of the screen is in an expanded state due to the low ionic strength of the water. When the filter element is in an operating state, part of the water is purified, resulting in a gradual increase in the ionic strength of the water, and the ion gel on the surface of the screen gradually contracts.

[0034] Preferably, in step S1, the polyolefin is polypropylene.

[0035] More preferably, the molecular weight of the polypropylene is 30,000-150,000, and the degree of polymerization of the polypropylene is 714-3571.

[0036] Preferably, in step S1, the diameter of the mesh of the separator is 0.1-0.5 mm, more preferably 0.3 mm-0.5 mm.

[0037] In the present invention, the interweaving step may be conventional in the art.

[0038] Preferably, the interweaving forming step is to extrude molten polyolefin through an extruder to obtain molten plastic filaments, and then interweave the plastic filaments to obtain a softened separator semi-finished product, and then cool and solidify it in a water bath.

[0039] In the present invention, the length of the polyolefin can be designed according to the sizes of the spacer, membrane and guide cloth in the final filter element structure.

[0040] Preferably, in step S1, the concentration of the tannic acid in the aqueous solution is 0.5 g / L-1 g / L.

[0041] Preferably, in step S1, the concentration of the polyethyleneimine in the aqueous solution is 0.2 g / L-0.5 g / L.

[0042] Preferably, in step S1, the soaking further includes the steps of taking out and cleaning.

[0043] More preferably, deionized water is used for the cleaning.

[0044] Preferably, in step S1, the soaking temperature is 23-27°C, for example 25°C.

[0045] Preferably, in step S1, the soaking time is 1-5 min, more preferably 3 min-5 min.

[0046] Preferably, in step S2, the concentration of the glycidyl methacrylate in the aqueous solution is 15 g / L-20 g / L.

[0047] Preferably, in step S2, the soaking step further includes the steps of taking out and washing;

[0048] More preferably, deionized water is used for the cleaning.

[0049] Preferably, in step S2, the soaking temperature is 40-60°C, more preferably 50-60°C.

[0050] Preferably, in step S2, the soaking time is 10-20 min, more preferably 15-20 min.

[0051] Preferably, in step S3, the concentration of the 2-acrylamide-2-methylpropanesulfonic acid in the mixed solution is 70 g / L-100 g / L.

[0052] Preferably, in step S3, the concentration of diethyl dimethacrylate in the mixed solution is 15 g / L-20 g / L.

[0053] Preferably, in step S3, the concentration of potassium persulfate in the mixed solution is 3 g / L.

[0054] Preferably, in step S3, the soaking step further includes the steps of taking out and washing;

[0055] More preferably, deionized water is used for the cleaning.

[0056] Preferably, in step S3, the soaking temperature is 60-80°C, more preferably 70-80°C.

[0057] Preferably, in step S3, the soaking time is 6-12 hours, more preferably 9-12 hours.

[0058] The present invention also provides a modified separator, which is made by the above preparation method.

[0059] The present invention also provides a method for preparing a filter element, which includes the above-mentioned modified spacer, and specifically comprises the following steps:

[0060] Stack the modified spacer, membrane and guide cloth in sequence, wind them on the central tube, seal the edges with glue and fix them with tape;

[0061] The modified separator, the membrane and the guide cloth have the same size;

[0062] The membrane is a reverse osmosis membrane or a nanofiltration membrane.

[0063] The present invention also provides a filter element, which is made by the above-mentioned preparation method.

[0064] The positive progress effect of the present invention is:

[0065] (1) The modified screen of the present invention has a self-cleaning function. In the present invention, an ion gel is constructed on the surface of the screen formed by interweaving polypropylene fibers. When the modified screen is in the static and running states of the filter element, the ion gel is in an expanded and contracted state, respectively. The expansion and contraction of the ion gel can destroy pollutants attached to the surface of the modified screen, reduce the adhesion of pollutants, and thus make the modified screen have a self-cleaning function.

[0066] (2) The modified screen of the present invention has a strong anti-pollution ability. On the one hand, since most pollutants in water bodies are negatively charged, the negatively charged active functional layer (2-acrylamide-2-methylpropanesulfonic acid is negatively charged) can achieve the anti-pollution property of the active functional layer through electrostatic repulsion; on the other hand, since the active functional layer is negatively charged and has strong hydrophilicity, a hydration layer can be formed on the surface of the functional layer, further improving the anti-pollution ability of the functional layer.

[0067] (3) Protect the diaphragm and prevent it from being scratched: During the filter element manufacturing process, the spacer mesh is in close contact with the diaphragm surface, and during the process of winding the filter element, the spacer mesh and the diaphragm will move relative to each other, so there is a risk of the diaphragm being scratched by the spacer mesh. However, after the fiber surface of the spacer mesh is loaded with ion gel, the ion gel is relatively soft and is not easy to scratch the diaphragm surface, thus playing a protective role. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 2 are zeta potential diagrams of the modified separators of Examples 1 to 3 and Comparative Example 2 and the separator surface of Comparative Example 1.

[0069] Figure 2 The operating performance diagram of the filter elements of Examples 1 to 3 and Comparative Examples 1 to 2 under tap water conditions is shown. DETAILED DESCRIPTION

[0070] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.

[0071] The reagents and raw materials used in the following examples, such as tannic acid, are all commercially available.

[0072] In the following embodiment, the size of the screen is 0.25m*0.5m, and the specific parameters are as follows:

[0073] The separator of Example 1: The diameter of the wire of the separator is 0.1 mm, the thickness of the separator is 0.2 mm, the molecular weight of the polypropylene is 84000, the degree of polymerization of the polypropylene is 2000, and the warp and weft density of the separator is 33 strands / in 2 .

[0074] The screen of Example 2: The diameter of the screen wire is 0.3 mm, the thickness is 0.6 mm, the molecular weight of polypropylene is 84,000, the degree of polymerization of polypropylene is 2,000, and the warp and weft density of the screen is 16 strands / in. 2 .

[0075] The separator of Example 3 has a mesh diameter of 0.5 mm, a thickness of 1 mm, a molecular weight of polypropylene of 84,000, a degree of polymerization of polypropylene of 2,000, and a warp and weft density of 7 strands / in. 2 .

[0076] In the following examples, the size of the nanofiltration membrane is 0.25m*0.5m, and the specific parameters are as follows:

[0077] The nanofiltration membrane is a polyamide nanofiltration membrane.

[0078] Nanofiltration membrane performance: water flux 12LMH / bar; desalination rate: MgSO4 removal rate 98%, NaCl removal rate 65%.

[0079] In the following embodiment, the size of the guide cloth is 0.25m*0.5m, and the specific parameters are as follows:

[0080] The guide cloth is made of polyethylene terephthalate, and the thickness of the guide cloth is 0.25 mm.

[0081] In the following embodiments, the extruder is a single-screw extruder, model SJ-45.

[0082] Example 1

[0083] S1. Molten polyolefin is extruded through an extruder to obtain molten plastic filaments, which are then interwoven to obtain a softened semi-finished spacer mesh. The semi-finished mesh is then cooled and solidified in a water bath to obtain the spacer mesh. The spacer mesh is then immersed in an aqueous solution of tannic acid and polyethyleneimine, wherein the volume of the aqueous solution is 0.25 L, the concentration of tannic acid is 0.1 g / L, and the concentration of polyethyleneimine is 0.05 g / L. The immersion temperature is 25°C, and after immersion for 1 minute, the mesh is removed and rinsed with deionized water.

[0084] S2. Soak the screen after soaking in step S1 in an aqueous solution of glycidyl methacrylate, wherein the volume of the aqueous solution is 0.25 L, the concentration of glycidyl methacrylate is 10 g / L, the soaking temperature is 40°C, and after soaking for 10 minutes, take it out and rinse it with deionized water.

[0085] S3. Soak the screen after soaking in step S2 in a mixed solution of 2-acrylamide-2-methylpropanesulfonic acid, diethanol dimethacrylate and potassium persulfate, wherein the volume of the mixed solution is 0.25 L, the concentration of 2-acrylamide-2-methylpropanesulfonic acid is 50 g / L, the concentration of diethanol dimethacrylate is 10 g / L, the concentration of potassium persulfate is 3 g / L, the soaking temperature is 60°C, and after soaking for 6 hours, take out and clean it with deionized water to obtain a modified screen.

[0086] The modified separator consists of an inner core and an outer layer. The inner core is a separator formed by interwoven polypropylene with tannic acid adsorbed on the separator. The outer layer is an ion gel with a thickness of 50 μm. The ion gel includes a cationic crosslinked network and an anionic crosslinked network. The cationic crosslinked network is formed by the crosslinking reaction between polyethyleneimine and tannic acid adsorbed on the separator, while the anionic crosslinked network is formed by the crosslinking reaction between 2-acrylamido-2-methylpropanesulfonic acid and diethanol dimethacrylate. The cationic and anionic crosslinked networks are connected by glycidyl methacrylate.

[0087] The modified separator, nanofiltration membrane and guide cloth are stacked in sequence, wound together on a central tube, sealed with glue and fixed with tape to form a filter element.

[0088] Example 2

[0089] S1. Molten polyolefin is extruded through an extruder to obtain molten plastic filaments, which are then interwoven to obtain a softened semi-finished spacer mesh. The semi-finished mesh is then cooled and solidified in a water bath to obtain the spacer mesh. The spacer mesh is then immersed in an aqueous solution of tannic acid and polyethyleneimine, wherein the volume of the aqueous solution is 0.25 L, the concentration of tannic acid is 0.5 g / L, and the concentration of polyethyleneimine is 0.2 g / L. The immersion temperature is 25°C, and after immersion for 3 minutes, the mesh is removed and rinsed with deionized water.

[0090] S2. Soak the screen after soaking in step S1 in an aqueous solution of glycidyl methacrylate, wherein the volume of the aqueous solution is 0.25 L, the concentration of glycidyl methacrylate is 15 g / L, the soaking temperature is 50°C, and after soaking for 15 minutes, take it out and rinse it with deionized water.

[0091] S3. Soak the screen after soaking in step S2 in a mixed solution of 2-acrylamide-2-methylpropanesulfonic acid, diethanol dimethacrylate and potassium persulfate, wherein the volume of the mixed solution is 0.25 L, the concentration of 2-acrylamide-2-methylpropanesulfonic acid is 70 g / L, the concentration of diethanol dimethacrylate is 15 g / L, the concentration of potassium persulfate is 3 g / L, the soaking temperature is 70°C, and after soaking for 9 hours, take out and clean it with deionized water to obtain a modified screen.

[0092] The modified separator consists of an inner core and an outer layer. The inner core is a polypropylene interwoven separator with tannic acid adsorbed on it. The outer layer is an ion gel with a thickness of 70 μm. The ion gel includes a cationic crosslinked network and an anionic crosslinked network. The cationic crosslinked network is formed by the crosslinking reaction between polyethyleneimine and the tannic acid adsorbed on the separator, while the anionic crosslinked network is formed by the crosslinking reaction between 2-acrylamide-2-methylpropanesulfonic acid and diethanol dimethacrylate. The cationic and anionic crosslinked networks are connected by glycidyl methacrylate.

[0093] The modified separator, nanofiltration membrane and guide cloth are stacked in sequence, wound together on a central tube, sealed with glue and fixed with tape to form a filter element.

[0094] Example 3

[0095] S1. Molten polyolefin is extruded through an extruder to obtain molten plastic filaments, which are then interwoven to obtain a softened semi-finished spacer mesh. The semi-finished mesh is then cooled and solidified in a water bath to obtain the spacer mesh. The spacer mesh is then immersed in an aqueous solution of tannic acid and polyethyleneimine, wherein the volume of the aqueous solution is 0.25 L, the concentration of tannic acid is 1 g / L, and the concentration of polyethyleneimine is 0.5 g / L. The immersion temperature is 25°C, and after immersion for 5 minutes, the mesh is removed and rinsed with deionized water.

[0096] S2. Soak the screen after soaking in step S1 in an aqueous solution of glycidyl methacrylate, wherein the volume of the aqueous solution is 0.25 L, the concentration of glycidyl methacrylate is 20 g / L, the soaking temperature is 60°C, and after soaking for 20 minutes, take it out and rinse it with deionized water.

[0097] S3. Soak the screen after soaking in step S2 in a mixed solution of 2-acrylamide-2-methylpropanesulfonic acid, diethanol dimethacrylate and potassium persulfate, wherein the volume of the mixed solution is 0.25L, the concentration of 2-acrylamide-2-methylpropanesulfonic acid is 100g / L, the concentration of diethanol dimethacrylate is 20g / L, the concentration of potassium persulfate is 3g / L, the soaking temperature is 80°C, and after soaking for 12h, take out and clean with deionized water to obtain a modified screen.

[0098] The modified separator consists of an inner core and an outer layer. The inner core is a polypropylene interwoven separator with tannic acid adsorbed on the separator. The outer layer is an ion gel with a thickness of 100 μm. The ion gel includes a cationic crosslinked network and an anionic crosslinked network. The cationic crosslinked network is formed by the crosslinking reaction between polyethyleneimine and the tannic acid adsorbed on the separator, while the anionic crosslinked network is formed by the crosslinking reaction between 2-acrylamide-2-methylpropanesulfonic acid and diethanol dimethacrylate. The cationic and anionic crosslinked networks are connected by glycidyl methacrylate.

[0099] The modified separator, nanofiltration membrane and guide cloth are stacked in sequence, wound together on a central tube, sealed with glue and fixed with tape to form a filter element.

[0100] Comparative Example 1

[0101] The separator net before modification in Example 1, the nanofiltration membrane and the guide cloth were stacked in sequence, wound together on the central tube, sealed with glue and fixed with tape to make a filter element.

[0102] Comparative Example 2

[0103] The screen before modification in Example 1 was soaked in an aqueous solution of tannic acid and polyethyleneimine, wherein the volume of the aqueous solution was 0.25 L, the concentration of tannic acid was 0.1 g / L, the concentration of polyethyleneimine was 0.05 g / L, and the soaking temperature was 25°C. After soaking for 1 minute, the screen was taken out and cleaned with deionized water to obtain a modified screen.

[0104] The modified separator, nanofiltration membrane and guide cloth are stacked in sequence, wound together on a central tube, sealed with glue and fixed with tape to form a filter element.

[0105] Effect Example 1: Test of Surface Charge

[0106] The surface charge of the modified screens of Examples 1 to 3 and Comparative Example 2 and the screen of Comparative Example 1 was tested using a zeta potential tester. Figure 1 As can be seen from Table 1, the charge of the screen before modification (Comparative Example 1) is relatively weak (isoelectric point is about 4.3), which is the case of conventional polymers in water. The negative charge of the modified screens of Examples 1 to 3 is significantly enhanced (isoelectric point <3), which is mainly due to the strong negative charge of the sulfonate ions in the ion gel. After modification, since the surface of the screen is loaded with a large amount of ion gel, the charge of the screen surface is mainly related to the ion gel, so the charge of Examples 1-3 is almost the same. On the contrary, in Comparative Example 2, only one modification was performed, and a large amount of cationic gel (polyethyleneimine is positively charged) was loaded on the surface, so the screen surface is positively charged, and the isoelectric point is 8.8 (>7).

[0107] Table 1 Isoelectric points of the modified separators of Examples 1 to 3 and the separators of Comparative Examples 1 to 2

[0108] Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Isoelectric point 4.3 8.8 2.9 2.5 2.6

[0109] Effect Example 2: Filter Element Operation Life Test

[0110] The operating performance of the filter elements of Examples 1 to 3 and Comparative Examples 1 to 2 was examined using tap water, wherein the filter elements were left to stand for 16 hours at every 2 ton flow rate and then continued to operate, for a total of 12 ton operation.

[0111] Table 2 Total flow of filter elements of Examples 1 to 3 and Comparative Examples 1 to 2

[0112]

[0113] from Figure 2 It can be seen that the filter element using the screen of Comparative Example 1 gradually experienced a decrease in flow rate, while the filter elements using the modified screens of Examples 1-3 and Comparative Example 2 experienced an increase in flow rate after 16 hours of standing, then gradually decreased during operation. Ultimately, compared to the filter element of Comparative Example 1, the filter element using the modified screens of Examples 1-3 achieved a significant increase in total flow rate by 15-30% (as shown in Table 2). Compared to Comparative Example 2, the filter element using the modified screens of Examples 1-3 also achieved a greater increase in total flow rate (as shown in Table 2).

[0114] Although specific embodiments of the present invention have been described above, those skilled in the art will appreciate that these are merely illustrative and that the scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, and such changes and modifications are intended to fall within the scope of the present invention.

Claims

1. A modified separator, characterized in that: The modified separator consists of two parts: an inner core and an outer layer; The inner core is a separator; the separator is formed by interweaving polyolefins; tannic acid is adsorbed on the separator; the outer layer is an ion gel; The thickness of the outer layer is 50-100 μm; The ion gel comprises a cationic cross-linked network and an anionic cross-linked network; The cationic cross-linked network is formed by a cross-linking reaction between polyethyleneimine and the tannic acid adsorbed on the separator; The anionic cross-linked network is formed by the cross-linking reaction of 2-acrylamide-2-methylpropanesulfonic acid and diethanol dimethacrylate; The cationic cross-linked network and the anionic cross-linked network are connected by glycidyl methacrylate.

2. The modified separator according to claim 1, characterized in that: The polyolefin is polypropylene; Preferably, the molecular weight of the polypropylene is 30,000-150,000, and the degree of polymerization of the polypropylene is 714-3571; And / or, the diameter of the mesh of the separator is 0.1-0.5 mm, preferably 0.3 mm-0.5 mm; And / or, the interweaving step comprises extruding molten polyolefin through an extruder to obtain molten plastic filaments, interweaving the plastic filaments to obtain a softened semi-finished spacer mesh, and cooling and solidifying the semi-finished mesh in a water bath; And / or, the thickness of the outer layer is 70-100 μm.

3. A method for preparing a modified separator, characterized in that: It includes the following steps: S1. Soak the screen in an aqueous solution of tannic acid and polyethyleneimine; Wherein, the separator is formed by interweaving polyolefins; Wherein, the concentration of the tannic acid in the aqueous solution is 0.1-1 g / L; Wherein, the concentration of the polyethyleneimine in the aqueous solution is 0.05-0.5 g / L; S2. The spacer obtained in step S1 is soaked in an aqueous solution of glycidyl methacrylate; Wherein, the concentration of glycidyl methacrylate in the aqueous solution is 10-20 g / L; S3. The screen obtained in step S2 was soaked in a mixed solution of 2-acrylamide-2-methylpropanesulfonic acid, diethanol dimethacrylate and potassium persulfate; Wherein, the concentration of the 2-acrylamide-2-methylpropanesulfonic acid in the mixed solution is 50-100 g / L; Wherein, the concentration of diethyl dimethacrylate in the mixed solution is 10-20 g / L; Wherein, the concentration of the potassium persulfate in the mixed solution is 3-5 g / L.

4. The method for preparing the modified separator according to claim 3, wherein: In step S1: The polyolefin is polypropylene; Preferably, the molecular weight of the polypropylene is 30,000-150,000, and the degree of polymerization of the polypropylene is 714-3571; And / or, the diameter of the mesh of the separator is 0.1-0.5 mm, preferably 0.3 mm-0.5 mm; And / or, the interweaving step comprises extruding molten polyolefin through an extruder to obtain molten plastic filaments, interweaving the plastic filaments to obtain a softened semi-finished spacer mesh, and cooling and solidifying the semi-finished mesh in a water bath; and / or, the concentration of the tannic acid in the aqueous solution is 0.5 g / L-1 g / L; and / or, the concentration of the polyethyleneimine in the aqueous solution is 0.2 g / L-0.5 g / L; And / or, the soaking further includes the steps of taking out and washing; Preferably, deionized water is used for cleaning; and / or, the soaking temperature is 23-27° C., for example 25° C.; And / or, the soaking time is 1-5 min, preferably 3-5 min.

5. The method for preparing the modified separator according to claim 3, wherein: In step S2: The concentration of the glycidyl methacrylate in the aqueous solution is 15 g / L-20 g / L; And / or, the soaking further includes the steps of taking out and washing; Preferably, deionized water is used for cleaning; And / or, the soaking temperature is 40-60°C, preferably 50-60°C; And / or, the soaking time is 10-20 minutes, preferably 15-20 minutes.

6. The method for preparing the modified separator according to claim 3, characterized in that: In step S3: The concentration of 2-acrylamide-2-methylpropanesulfonic acid in the mixed solution is 70 g / L-100 g / L; And / or, the concentration of diethyl dimethacrylate in the mixed solution is 15 g / L-20 g / L.

7. The method for preparing the modified separator according to claim 3, characterized in that: In step S3, after soaking, the steps of taking out and washing are also included; Preferably, deionized water is used for cleaning; And / or, the soaking temperature is 60-80°C, preferably 70-80°C; And / or, the soaking time is 6-12 hours, preferably 9-12 hours.

8. A modified separator, characterized in that: The modified separator is made by the preparation method according to any one of claims 3 to 7.

9. A method for preparing a filter element, characterized in that: The modified spacer according to claim 8 comprises the following steps: The modified spacer, membrane and guide cloth are stacked in sequence, wound on the central tube, sealed with glue and fixed with tape; The modified separator, the membrane and the guide cloth have the same size; The membrane is a reverse osmosis membrane or a nanofiltration membrane.

10. A filter element, characterized in that: The filter element is made by the filter element preparation method according to claim 9.